The Role of Teacher Interpersonal Communication in Increasing Children's Knowledge - Martha, Layung Paramesti; Suchyadi, Yudhie (UNIVERSITAS PAKUAN, 2023)
intends to find out how the communication process used by the teacher in the teaching and learning process, the forms of communication and communication approaches that the teacher makes towards students. By involving 3 basic informants and 7 supporting informants, namely teachers and parents of students who often monitor their children at school. This study uses qualitative research methods with data collection techniques using observation, in-depth interviews, and document studies as well as descriptive data analysis techniques with percentages. The formulation of the problem of this research is how is the role of the teacher's interpersonal communication in increasing children's knowledge. Based on the results of the existing research and discussion, what can be concluded in this study regarding the Role of Teacher Interpersonal Communication in Improving Children's Knowledge are as follows: (1). Overall, the role of teacher interpersonal communication in increasing children's knowledge is quite good. (2). The language used by the teacher is very appropriate in communicating with their students. (3). Non-verbal communication carried out by the teacher in interacting with his students is by using movements, additional objects, gestures, facial expressions and symbols, and various sound intonations. (4). The messages conveyed in teacher-student interpersonal communication are more about the concept of the lesson and also motivate students to more quickly understand what the teacher means.